Evolución de los sistemas inteligentes de transporte y actualidad en Colombia - Ochoa Borja, Carlos Alberto (Ingenierias, 2019)
The aim of this document is to present a review of the historical development of intelligent transportation systems. From the days of the Egyptian Pharaohs and the Roman legions where the roads were decisive for communication and economy, later with the industrial revolution came improvements in the construction of roads, railways and airplanes; Then we find the evolution of Intelligent Transportation Systems (ITS) in the USA, Japan and Europe. The identified papers and technologies are crucial to assess the development of the past and present time. Today, in the information age, there is a search for the global economic efficiency, governed by environmental concerns, economic alliances and trade agreements. In this work we have also a description of SIT components such as GPS, maps, route planning, sensors, communications, transport control and traffic in its general scope, including the solution of problems such as accidents, environmental pollution and traffic congestion